Potensi Ekonomi Kreatif Dalam Mengatasi Pengangguran di Provinsi Kalimantan Tengah - Riza Supian; Alexandra Hukom (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
Unemployment ia is a problem that is always faced in economic develovment, good or bad of the economy in a region is caused by one of them the level of unemployment. The creative economy focused more on developing on idea or idea with inovation, creativity so tat it can crate new jobs so that it does no defend on the unemployment, that right strategy is needed so that it can be a solution of the problem of unemployment. The reserch uses a qualitativ method of dedcriptive analysis and uses SWOT analysis of internal adan external factors. Based on the result of the analysis, the creative economy is in a favorable position or has the strenght to overcome exsiting threats. The creative economy can be solution in overcoming the problem of unemployment in central Kalimantan if it can be maneged properly by using appropiate strategies.